Hubungan Beban Glikemik, Aktivitas Fisik, Stres Kerja Dengan Lemak Visceral Pada Pekerja Di Dinas Tenaga Kerja Dan Transmigrasi Provinsi Banten - Erlita Cahaya Rizkiah; Nadiyah Nadiyah; Anugrah Novianti; Nazhif Gifari; Mertien Sapang (Pusat Riset dan Inovasi Nasional, 2023)
Background: Visceral fat is fat that is stored in the adipose tissue of the abdominal region. The accumulation of high amounts of visceral fat causes central obesity and the occurrence of metabolic syndrome which is a risk for degenerative diseases. Banten Province shows that the prevalence of obesity in 2018 is 22.5% and in 2020 it is 25.2%. Risk factors that cause obesity, especially in the workplace, are lack of physical activity, unhealthy eating patterns, and unhealthy lifestyles. Objective: to determine the relationship between glycemic load, physical activity, and work stress with visceral fat. Methods: The research was carried out in the Office of Manpower and Transmigration of Banten Province, from August 2021 to August 2022. This type of research is quantitative research which is an analytic survey using a cross-sectional research design with a research sample of 76 respondents. Data analysis used the Chi-Square test. Results: There was a relationship between glycemic load and visceral fat (p=0.000), there was a relationship between physical activity and visceral fat (p=0.002), and there was no relationship between work stress and visceral fat (p=0.137). This is because respondents still consume sufficient carbohydrate food on weekdays and holidays and respondents tend to do less physical activity which causes fat accumulation in the body.Conclusion: There is a significant relationship between glycemic load and physical activity to the formation of visceral fat.